2023
DOI: 10.1002/asi.24755
|View full text |Cite
|
Sign up to set email alerts
|

Why are coauthored academic articles more cited: Higher quality or larger audience?

Abstract: Collaboration is encouraged because it is believed to improve academic research, supported by indirect evidence in the form of more coauthored articles being more cited. Nevertheless, this might not reflect quality but increased self-citations or the "audience effect": citations from increased awareness through multiple author networks. We address this with the first science wide investigation into whether author numbers associate with journal article quality, using expert peer quality judgments for 122,331 ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 56 publications
1
2
0
Order By: Relevance
“…Despite the claims for multidisciplinary research, this has very few, if any, impacts on citations. In parallel to earlier studies claiming that co-authored papers attract more citations (e.g., Thelwall et al, 2023), other networks are essential and significantly acclaimed, but two authors seem sufficient to write a paper to be cited. More than three is too many despite the debate that collaborations would help reduce the workload of multiple authors.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Despite the claims for multidisciplinary research, this has very few, if any, impacts on citations. In parallel to earlier studies claiming that co-authored papers attract more citations (e.g., Thelwall et al, 2023), other networks are essential and significantly acclaimed, but two authors seem sufficient to write a paper to be cited. More than three is too many despite the debate that collaborations would help reduce the workload of multiple authors.…”
Section: Discussionsupporting
confidence: 57%
“…The number of authors per article is used in the literature as a proxy for collaborations to explain citations (Haslam et al, 2008;Yu et al, 2014, among others). Evidence has also suggested that co-authored articles will likely receive more citations (Thelwall et al, 2023). The impact on citations proved significant even if this means some halo effect as more authors promote the article.…”
Section: Network and Collaboration In Tourism Researchmentioning
confidence: 99%
“…There are moderately strong Spearman correlations between author numbers and REF2021 quality scores (0.2–0.4) in medicine and the health, life, and physical sciences, but little or no positive association in engineering and the social sciences. In contrast, there was no evidence of association in the arts and humanities, and the decision sciences seemed to benefit from fewer authors (Thelwall, Kousha, Abdoli, Stuart, Makita, Wilson, & Levitt, 2023d). For the United Kingdom, after controlling for the effect of collaboration, having international (rather than national) co‐authors associates with higher quality research in 27 out of the 34 Units of Assessment, with collaboration with other advanced economies being particularly advantageous and collaboration with weaker economies tending to be a disadvantage from a quality perspective (Thelwall et al, 2022d).…”
Section: Factors Associating With Journal Article Qualitymentioning
confidence: 99%
“…Early examples include Frame & Carpenter (1979) and later studies have confirmed the trends towards increased international collaboration and networks in science (see e.g., Adams 2012;2013). Studies of international collaboration have also moved forward with conceptual clarifications (e.g., Katz & Martin, 1997), new indicators, e.g., of collaboration intensity (Coccia, & Bozeman 2016;Fuchs et al, 2021;Luukkonen et al, 1992), new visualization technologies (e.g., Van Eck & Waltman, 2014) and utilizing additional databases such as Scopus (Fu et al 2022) Also, international collaboration (or collaboration more generally) has been addressed from a citation impact perspective, showing that such papers tend to be cited more than other articles (see e.g., Thelwall et al 2023a).…”
Section: Introductionmentioning
confidence: 99%